In a state of dilapidation - Mumbai Archive Project Team (Jio Institute, 2024)
Over time, the living spaces have deteriorated with each monsoon. Dilapidation and dampness have caused paint to peel off the walls, and cracks have appeared in several places due to a lack of renovation.